Livestock related nutrient budgets within village territories in western Niger - Schlecht, Eva; Hiernaux, Pierre H.Y.; Achard, F.; Turner, M.D. (Springer, 2004)
Poor cropland fertility and a rapidly rising demand for food force Sahelian farmers to cultivate more land and shorten fallow periods. This mostly leads to a gradual decline in crop yields per hectare, which can be counterbalanced by the systematic use of livestock manure on cropland. To assess the potential and limits of manuring practices, annual nutrient budgets were established for different land-use types, based on forage and crop yields and livestock and cropland management in five village territories in western Niger, which were selected along the Sahelian climatic gradient. Stocking rates per km2 of pasturing area range from 8–22 tropical livestock units (TLU, animal of 250 kg live weight). Faecal excretion during grazing directly returns 18–25% of the consumed forage dry matter, 21–29% of the ingested nitrogen and 44–56% of ingested phosphorus to the grazed land. Corralling animals on fields at night leads to a spatial concentration of nutrients, benefiting at most 9% of the arable village land. Where livestock consume only 15–20% of the total amount of forage produced, there is some scope for increasing village livestock numbers in order to increase the area manured, but eventually manuring must be complemented by additional measures such as the application of inorganic fertilizers to sustain overall productivity of the farming systems.